An efficient synthesis of substituted chrysenes - Eccleshare, Lee; Selzer, Sean; Woodward, Simon (Elsevier, 2017)
Substituted chrysenes have been swiftly synthesised by the 6-endo-dig cyclisation of ethynylnaphthalenes using platinum(II) chloride. Cyclisation precursors were directly prepared from commercially available 2-bromoaldehydes in a telescoped synthetic procedure involving a Cannizzaro triggered cascade and subsequent dehydration and desilylation. This short synthetic procedure allows rapid access to derivatives of biologically active molecules with useful electronic properties.